Properties of mortar with natural cockle shell waste as partial sand replacement - Hanis Nadiah, Ruslan (2022)
River sand is the most used building material in the construction industry. However, extensive usage of river sand would pose undesirable threat to the river environment and also can result in the depletion of this natural resource in future. Meanwhile, the prospering cockle trade generates cockle shell wastes which are disposed of at dumping sites. Thus, existing approach in disposing of cockle shell wastes causes environmental pollution. In view of sustainable construction and healthier environment, the approach of utilizing crushed cockle shells as sand replacement in mortar would be able to minimize the amount of river sand consumed in the construction industry and reduce cockle shell waste disposal. Research on the utilization of cockle shell waste as mixing ingredient in mortar is limited. The effect of integrating cockle shells as partial sand replacement towards mechanical properties and durability of mortar is unknown. The present research investigated the effects of crushed cockle shells as sand replacement on performance of mortar. The objective of this study was to determine the effects of crushed cockle shells as sand replacement on fresh properties, mechanical properties, durability properties and other properties of mortar. A total of five mortar mixtures were employed. Mortar mixes containing various levels of percentage of crushed cockle shells at 0%, 10%, 20%, 30% and 40% by weight of river sand were prepared. Two types of curing conditions were applied, namely, water and air, until the testing age. Flowability test, fresh density test, compressive strength test, flexural strength test and dynamic modulus elasticity test were conducted. Then, the Response Surface Methodology (RSM) was used for modelling and optimization the mechanical properties of mortar. Other than that, water absorption, volume permeable void, carbonation test, acid resistance, and sulphate resistance were conducted to determine the durability of mortar. For other properties, fire resistance was also examined. The findings have shown that the use of 10 % crushed cockle shell as sand replacement increased the flowability and mechanical properties of the mortar as compared to those of the 0% mortar. Integration of crushed cockle shell formed denser internal structure of mortar resulting in it exhibiting the lowest water absorption value and volume permeable void amongst all mixes. Water-cured specimens yielded better results compared to air-cured specimens. Incorporation of crushed cockle shell influenced the performance of mortar when exposed to carbonation test and immersed in acid. It was evident that 10% crushed cockle shell mortar resulted the higher carbonation depth compared to 0% mortar. In terms of acid resistance, the mortar specimens containing 10% crushed cockle shell experience more deterioration as compared to 0% mortar after immersed in hydrochloric acid solution. It is interesting to note that, 10% crushed cockle shells mortar exhibited better durability when exposed to sulphate solution. The mass change and strength loss of the specimens were lesser with -0.11% and 7.09% than those of the -0.2% and 16.47% for 0% mortar. Mortar containing 10% content of crushed cockle shell recorded more mass loss and strength reduction in comparison to the mix without cockle shells when exposed to elevated temperature. On overall, incorporation of 10% of crushed cockle shells as sand replacement in mortar increases its mechanical properties. Success in producing sustainable mortar using cockle shell waste would contribute towards cleaner environment and sustainable construction for healthier life of nation.